The Greatest Show : Stories - Downs, Michael, 1964- (Book collections on Project MUSE., 2012)
Fire sweeps along the wall of a circus tent while inside thousands of people enjoy a Ringling Brothers and Barnum and Bailey matinee. Within minutes, flames consume the canvas and vast sections collapse, killing 168 people and injuring hundreds more. Inspired by the 1944 Hartford Circus Fire, the interconnected stories in Michael Downs's The Greatest Show explore the aftermath of a disaster in a world of clowns, elephants, and childhood fantasies. In the opening story, Ania Liszak, a young Polish housemaid, steals circus tickets from her employer to take her three-year-old son, Teddy, to the ma.